Phytochemicals in fruits of Hawaiian wild cranberry relatives. (20th November 2013) - Hummer, Kim; Durst, Robert; Zee, Francis; Atnip, Allison; Giusti, M Monica
Abstract BACKGROUND Cranberries (Vaccinium macrocarpon Ait.) contain high levels of phytochemicals such as proanthocyanidins (PACs). These polymeric condensations of flavan‐3‐ol monomers are associated with health benefits. Our objective was to evaluate phytochemicals in fruit from Hawaiian cranberry relatives, V. reticulatum Sm. and V. calycinum Sm. Normal‐phase HPLC coupled with fluorescence and ESI‐MS detected PACs; the colorimetric 4‐dimethylaminocinnamaldehyde (DMAC) assay was used to determine total PACs. Spectrophotometric tests and reverse‐phase HPLC coupled to photodiode array and refractive index detectors evaluated phenolics, sugars, and organic acids. Antioxidant capacity was determined by the ORAC and FRAP assays. RESULTS Antioxidant capacities of Hawaiian berries were high. The FRAP measurement for V. calycinum was 454.7 ± 90.2 µmol L−1 Trolox equivalents kg−1 for pressed fruit. Hawaiian berries had lower peonidin, quinic and citric acids amounts and invert (∼1) glucose/fructose ratio compared with cranberry. Both Hawaiian Vaccinium species were good sources of PACs; they contained phenolics and PAC monomers, A and B‐type trimers, tetramers and larger polymers. Vaccinium reticulatum and V. calycinum showed comparable or higher PAC levels than in cranberry. Cranberries had higher percentage of A‐type dimers than did V. reticulatum. A and B‐type dimers were not differentiated in V. calycinum. The total PACs (as measured by DMAC) for V. calycinum (24.3 ± 0.10 mg catechin equivalents kg−1) were about twice that in cranberry. CONCLUSION Berries of V. reticulatum and V. calycinum could serve as a rich dietary source of PACs, comparable to or greater than cranberries. These finding suggest that Hawaiian Vaccinium berries could be a functional food. Additional examination of the phytochemicals in other wild Vaccinium species is warranted. © 2013 Society of Chemical Industry